2019
DOI: 10.3389/fmicb.2019.01708
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolutionary Analysis of Potato Virus Y Infecting Potato Based on the VPg Gene

Abstract: Potato virus Y (PVY) is an important plant pathogen infecting solanaceous crops, causing significant losses to global potato and tobacco production. Some aspects of the plant pathology and molecular biology of PVY have been studied intensively, but the evolutionary dynamics of this virus are poorly understood. Here, we performed a comprehensive set of rigorous evolutionary analyses using 177 nucleotide sequences of the viral genome linked protein (VPg) gene, which interacts with the plant eukaryotic translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 65 publications
(79 reference statements)
1
19
0
Order By: Relevance
“…In contrast, Clades N and O experienced similar population expansions in the past few decades prior to a more recent decline. This is in accordance with a recent demographic analysis by Mao et al. (2019) , which suggested that the population of Clade N was associated with the global history of potato production.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, Clades N and O experienced similar population expansions in the past few decades prior to a more recent decline. This is in accordance with a recent demographic analysis by Mao et al. (2019) , which suggested that the population of Clade N was associated with the global history of potato production.…”
Section: Discussionsupporting
confidence: 93%
“…2019 ). However, an analysis of 176 VPg sequences (564 nt) placed the divergence between the N and O phylogroups at 1750 CE–1948 CE ( Mao et al. 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…CP genes were also used to obtain a recent estimate [104] of 129-169 YBP as the age of the present narcissus late season yellows virus population. However, most dating studies of potyviruses have been of PVY and TuMV populations (Table 1) and are based on gene sequences varying from full length ORFs of more than 9000 nts to the VPg gene of only 564 nts [29,30,100,105,106]. The results show an interesting and unexpected positive correlation between the length of the sequence and its estimated TMRCA (Table 1); the longer the sequence analyzed, the older the apparent age of the common ancestor.…”
Section: Potyviruses In Space and Timementioning
confidence: 99%
“…Studies on historical isolates preserved since the 1970s and 1980s from the Andean region of South America and Europe provide examples. With PVY, a dating study without these historical isolates suggested the "time to most common ancestor" (TMRCA) of PVY was the 16th century [105], whereas a similar study which included sequences from European isolates from the 1980s [158] placed its TMRCA around 1000 CE [106]. When new PVY isolates from the Andean potato domestication center were included in dating analyses, along with the 1980s European sequences, the TMRCA was estimated to be around 156 CE [29].…”
Section: Historical Potyvirus Specimensmentioning
confidence: 99%
“…While the potato-PVY analysis was based on the sample collection dates over several decades, onion-IYSV interactions are relatively new and hence predicting the phylodynamic patterns and demographic history of IYSV require more such data on temporal scale. The PVY demographic history and population expansion was deduced and compared with that of geographic distribution of host (potato) suggesting direct influence of potato cultivation area on the population size of the virus ( Mao et al, 2019 ). In this context, further studies how expansion of onion cultivation area influences the population expansion of IYSV will be interesting.…”
Section: Discussionmentioning
confidence: 99%